2004
DOI: 10.1073/pnas.0401200101
|View full text |Cite
|
Sign up to set email alerts
|

Improving vision in adult amblyopia by perceptual learning

Abstract: Practicing certain visual tasks leads, as a result of a process termed ''perceptual learning,'' to a significant improvement in performance. Learning is specific for basic stimulus features such as local orientation, retinal location, and eye of presentation, suggesting modification of neuronal processes at the primary visual cortex in adults. It is not known, however, whether such low-level learning affects higher-level visual tasks such as recognition. By systematic low-level training of an adult visual syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
409
3
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(464 citation statements)
references
References 37 publications
44
409
3
8
Order By: Relevance
“…Whereas the earliest attempts, such as training on vernier alignment (Levi & Polat 1996), showed only limited generalization beyond the specific trained target orientation, later attempts to ameliorate the deficient spatial interactions in low-level vision in amblyopia by perceptual training led to improvement of other aspects of vision such as Snellen acuity, counting and contrast sensitivity (e.g. Polat et al 2004;Levi 2005;Zhou et al 2006;Li et al 2007; see also Levi & Li 2009). …”
Section: The Present and Potential Future Impact Of Work On Animal Momentioning
confidence: 99%
“…Whereas the earliest attempts, such as training on vernier alignment (Levi & Polat 1996), showed only limited generalization beyond the specific trained target orientation, later attempts to ameliorate the deficient spatial interactions in low-level vision in amblyopia by perceptual training led to improvement of other aspects of vision such as Snellen acuity, counting and contrast sensitivity (e.g. Polat et al 2004;Levi 2005;Zhou et al 2006;Li et al 2007; see also Levi & Li 2009). …”
Section: The Present and Potential Future Impact Of Work On Animal Momentioning
confidence: 99%
“…Strikingly, an increasing number of clinical studies have reported that repetitive visual training based on sensory enrichment procedures may represent a very useful approach for the treatment of amblyopia, providing substantial improvement in a variety of visual tasks [76][77][78][79] (for a review, see Polat 80 and Levi and Li 81 ). One caveat to the therapeutic value of these visual practice procedures, however, is the narrow specificity of achievable improvement, which is typically limited to the selected trained stimulus, condition or task.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…For example, in a study investigating the effects of offline theta burst stimulation on a subsequent visual motion discrimination task, Silvanto and colleagues (Silvanto, Muggleton, Cowy & Walsh, 2007) found that external induction of neuronal plasticity (such as in the case of brain stimulation) also depends on the state of the targeted neurons during stimulation. Despite here induction of neural plasticity was found with above-threshold (simple) stimuli, larger improvements in tasks via perceptual learning (and thus neural plasticity) typically occur with more challenging, near-threshold stimuli (Polat et al, 2004;Sagi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…So far, PL has been shown to be effective in improving, among other dysfunctions, visual abilities in amblyopia (Campana, Camilleri, Pavan, Veronese, & Lo Giudice, 2014;Hussain, Webb, Astle, & McGraw, 2012;Levi & Li, 2009;Li, Young, Hoenig, & Levi, 2005;Polat, 2009;Polat, Ma-Naim, Belkin, & Sagi, 2004;Zhou, et al, 2006), mild refractive defects like myopia (Camilleri, Pavan, Ghin, Battaglini, et al, 2014;Tan & Fong, 2008) and presbyopia (Polat, et al, 2012), and central or peripheral vision loss and cortical blindness (Chung, 2011;Das, Tadin, & Huxlin, 2014;Huxlin, et al, 2009;Kasten, et al, 1998;Plank, et al, 2014;Rosengarth, et al, 2013;Sabel, Kenkel, & Kasten, 2005). In myopia, visual input is limited by an optical de-focus, despite normal neuronal connectivity and image processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation